PENGARUH ASOSIASI MEREK DAN KARAKTERISTIK PRODUK TERHADAP LOYALITAS MEREK COCACOLA (STUDI PERSEPSI KONSUMEN PEKANBARU) - Destina Apini Daulai; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of the study is to review singer determine the effect trademark association (x1) and product characteristics (x2) against brand loyalty (y) on light beverage products cocacola ( consumer perception study pekanbaru ) . Singer research method is quantitative hearts with using spss 21 , where samples which are used namely consumer the product consumes cocacola with counted 100 orangutan respondents sampling technique is accidental sampling using the formula slovin . Research results show that the test results operating simultaneous tin from the findings of f count is 108.065 while f tables 3.090 . It singer means f count> f table and significant value 0,000 < alpha of 0.05 . Means the association brands and products operating characteristics simultaneously influence significantly operate against brand loyalty on products soft drinks cocacola .Keywords : Associate Brands , Product Characteristics , Brand Loyalty